Authentication and Secure Robot Communication. (5th February 2014) - Yfantis, Evangelos A.; Fayed, Ahmad
In many cases robots are connected wirelessly with a file server and often with one another, either directly, or via the file server. The network connections form a subnet where the router has the static IP address visible to the outside world and the server along with the robots form a subnet with local IP addresses. Often however, each robot has its own static IP address. In addition, each robot has a NIC card and a unique NIC address, as well as other hardware identifiers depending on the functionality and complexity of the robot. The non-electronic part of the robot hardware usually represents mature technology that has been understood for a long time. The electronic hardware has evolved to the point that the embedded software can provide the needed intelligence for the robot to perform sophisticated tasks previously performed by one or more human beings. However, in previous research emphasis has been placed on the tasks performed by the robots, neglecting any security issues or liabilities that may arise due to lack of security. In this paper, we provide an algorithm for secure key management, and secure communication in an insecure wireless and noisy environment in which the robots operate.